2015
DOI: 10.17780/ksujes.25352
|View full text |Cite
|
Sign up to set email alerts
|

Use the Extended Activated Sludge Process to Remove Triclosan (TCS) from Wastewater Treatment Plant

Abstract: ABSTRACT:The antibacterial personal care product Triclosan (TCS), is a broad spectrum antibacterial. It has been used for more than 40 years as an antiseptic, disinfectant or preservative in clinical settings, and in the various consumer products including cosmetics, plastic materials and toys. It has lately been determined in the sources of the aquatic environment; its potential effect on ecosystems. The contaminants can reach the soil and aquatic environment through land application of wastewater effluent an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…ACS serves as a most promising biological method in removal of TCS. With an increase in the hydraulic retention time (HRT) upto 52 h, it has been observed to an increase in the removal efficiency up to 99.9% [38], the acclimation capacity of bacterial feed to the surroundings and has a major role in removal efficiency [37,38]. In the literature 80% of TCS removal with ACS is attributed to the mineralisation of compound to CO 2 and therefore concluded that biological degradation is the main removal mechanism for most of the compound and a removal efficiency of 96% has been observed [39].…”
Section: Biological Processmentioning
confidence: 99%
“…ACS serves as a most promising biological method in removal of TCS. With an increase in the hydraulic retention time (HRT) upto 52 h, it has been observed to an increase in the removal efficiency up to 99.9% [38], the acclimation capacity of bacterial feed to the surroundings and has a major role in removal efficiency [37,38]. In the literature 80% of TCS removal with ACS is attributed to the mineralisation of compound to CO 2 and therefore concluded that biological degradation is the main removal mechanism for most of the compound and a removal efficiency of 96% has been observed [39].…”
Section: Biological Processmentioning
confidence: 99%